Learned Ignorance in the Medicine Bow Mountains a Reflection on Intellectual Prejudice. - Clifford, Craig (Value Inquiry Book Series, 2008)
This book is an apologia for the rooted intellectual against the disdainful condescension of the cosmopolitan intellectual—an apology in the Socratic sense of the word. It reflects the author’s Texas rootedness unapologetically and offers a polemical but thoughtful indictment of the intellectual prejudice against rootedness; but it is ultimately about the universal human struggle with origins.